Influencing factors of survival rate after replantation of severed palm and fingers and related nursing strategies (断指断掌再植术后成活率影响因素分析及护理对策) - WEI Suhui (韦素惠); MO Julian (莫菊莲); TENG Lichu (滕立初) (中西医结合护理)
Objective To investigate the influencing factors of survival rate after replantation of severed palm and fingers and related nursing strategies. Methods The clinical data of 68 patients undergoing replantation of severed palm or severed finger were retrospectively analyzed. Univariate analysis and logistic regression model were performed to identify potential factors influencing the survival rate after replantation. Results There were 43 patients whose amputated finger(s) or palm survived after replantation. The logistic regressive analysis showed that completely severed injury, long time before admission, poor elasticity of the soft tissues of the finger pulp, poor capillary refilling reaction after surgery, purple or blue finger(s), development of thrombosis, vasospasm and severe anxiety were independent factors influencing the survival rate after replantation. Conclusion Influencing factors of survival rate after replantation included completely severed injury, long time before admission, low skin temperature after surgery, poor elasticity of the soft tissues of the finger pulp, poor capillary refilling reaction after surgery, purple or blue finger, development of thrombosis, vasospasm and severe anxiety. Targeted nursing interventions should be carried out to improve the survival rate after replantation. (目的 探讨断指断掌再植术后影响成活率的相关因素及护理对策。方法 回顾性分析2013年1月—2019年12月医院骨外科收治的68例断指断掌行再植术患者的临床资料, 应用Logistic回归分析影响再植成活率的危险因素, 并探讨相应的护理措施。结果 68例患者中再植成活43例, 再植未成活25例。Logistic回归分析结果显示, 完全离断、伤后就诊时间长 、术后指腹弹性差 、术后毛细血管反应差 、术后断指颜色一般 、有血栓形成 、有血管痉挛 、重度焦虑为影响断指断掌再植术后成活率的独立危险因素 (P<0. 05)。结论 完全离断、伤后就诊时间长、术后指腹弹性差、术后毛细血管反应差、术后断指颜色一般、有血栓形成、有血管痉挛、重度焦虑为影响断指断掌再植术后成活率的危险因素, 应采取积极的护理对策, 提高断指再植的成活率。)